PENGARUH KETERLIBATAN KERJA DAN KEPUASAN KERJA TERHADAP KEINGINAN BERPINDAH PADA KARYAWAN PT. GLOBAL NIKEL MULTIGUNA TANGERANG - Lita Hairiah; Roni Faslah (Jurnal Ilmiah Econosains, 2017)
This research aims to determine whether there is influence between job involvement and job satisfaction toward turnover intention on employees of PT. Global Nikel Multiguna. This research was carried out for 3 months, started from February to May 2015. The method used is a survey method. The population in this research were all employees of PT. GLOBAL NIKEL MULTIGUNA, amounting 85 employees and researchers took samples used as many as 68 employees by using random sampling technique. The instrument used of obtain data on the variables X1 (Job Involvement), X2 (Job Satitisfaction), and Y (Turnover Intention) was measured using questionnaire with Likert scale for X1 and Y, and using semantic differentials for X2. Then the data was tested for the validity and reliability, analysis through multiple regression techniques and classical assumption. The hypothesis was tested with significant the margin of error of 0.05 using t-test and analysis of variance (ANOVA). The results showed siginificant relationship between job involvement and job satisfaction on turnover intention of employees with regression equation Ŷ = 122.353 – 0.561X1 – 0.198X2. from the analysis of data, obtaining Fcount is 27.442 > Ftable = 3.14. this means that the hypothesis that there is significant relationship between job involvement and job satisfaction on turnover intention ef employees received. Meanwhile, the coefficient of determination for R2 is 45.8% while remaining 54.2% is influence by other factors not examined. Based on the above results, it is advisable for the leader of the company to give freedom of speech to the employees and provide corresponds salary whose contribute in the company in order to surpress levels of turnover intention on employees at the company. Keyword: Job Involvement, Job Satisfaction and Turnover Intention